Changes in Cardiac Varices and Their Clinical Significance after Eradication of Esophageal Varices by Band Ligation - Seung Woon Park; Yeon Seok Seo; Han Ah Lee; Sang Jung Park; Tae Hyung Kim; Jae Min Lee; Sang Jun Suh; Hyuk Soon Choi; Eun Sun Kim; Bora Keum; Young Kul Jung; Ji Hoon Kim; et al. (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. Cardiac varices (CVs) in patients with type 1 gastroesophageal varices (GOV1s) usually disappear with treatment for esophageal varices (EVs) by endoscopic injection sclerotherapy (EIS). However, whether this applies to patients treated with endoscopic band ligation (EBL) for EVs remains unclear. We evaluated the effect of EVs eradication by EBL on CVs. Methods. We included cirrhotic patients whose EVs had been eradicated using EBL and excluded those who had been treated using EIS, those who had received endoscopic therapy for CVs, and those who were combined with hepatocellular carcinoma. Results. A total of 123 patients were enrolled. The age was 59.7 ± 11.7 years, and 96 patients (78.0%) were men. Thirty-eight patients (30.9%) had EVs only, while 85 (69.1%) had GOV1s. After EVs eradication, the CVs disappeared in 55 patients (64.7%). EVs recurred in 40 patients, with recurrence rates at 1, 2, and 3 years of 16.0%, 29.6%, and 35.6%, respectively, the recurrence being more frequent in patients who had undergone EBL for secondary prophylaxis and in those with persisting CVs after EVs eradication (P=0.003). Conclusions. CVs frequently disappeared when EVs were eradicated using EBL in patients with GOV1s. Persistence of CVs after EVs eradication by EBL was associated with EVs recurrence.